Mahatma Gandhi and Vydūnas - Bagdonavičius, Vaclovas (Problemos, 1969)
There is much in common between the prominent Indian public and political figure, the leader of the national liberation movement Mahatma Gandhi (1869- 1948) and the distinguished Lithuanian cultural worker in Eastern Prussia Vydūnas (1868-1953). They lived and worked at much the same time and in nearly analogous conditions. India suffered the yoke of English colonizers, whereas Lithuanians were subject to intensive germanization. Analogous political conditions and the same philosophical source – the ancient Indian philosophy have formed nearly identical philosophical views and social activity principles of Gandhi and Vydūnas. Both in social activity and private life they were guided by the following principles: the fate of a man, nation and all mankind depends on the perfection of ethics and man’s spiritual world. The principle method of their struggle: passive resistance.